Permeability Evolution of a Cemented Volcanic Ash During Carbonation and CO2 Depressurization. Issue 10 (9th October 2018) - Clark, A. C.; MacFarlane, J.; Vanorio, T.
Abstract: The presence of calcium‐cemented ash beds serving as caprocks in hydrothermal systems calls for the examination of any chemo‐mechanical processes that may undermine or enhance their sealing capacity. Understanding these processes provides new information regarding how to model time‐dependent observations associated with seismicity and/or deformation in volcanic areas. In addition, since these ash beds are inherently similar to ash‐based concrete, a bridge of knowledge can be built across disciplines in the earth sciences and engineering. This paper investigates how the permeability of a volcanic ash cemented with hydrated lime changes upon exposure to carbon dioxide (CO2 ) in humid and hydrous conditions relevant to natural or human‐driven processes such as those found in hydrothermal settings or near wellbores used for secondary oil recovery, CO2 plume geothermal energy, or carbon storage. We characterized samples by their permeability during carbonation and subsequent changes in pore pressure and confining pressure. Products from the reaction of CO2 with the cemented ash matrix reduced permeability and entrapped fluids. The regions within samples permeated with unreacted CO2 were susceptible to fracturing upon rapid depressurization, but only when the effective stress state was sufficiently low. Altogether, the results indicate that lime‐cemented volcanic ash beds are particularly suited to act as flow barriers to CO2 ‐rich fluids. Plain Language Summary: This paper examines some of the physical characteristics of materials that are comprised of volcanic sediments and cemented together by a lime‐rich fluid. Such materials can be described as either concrete‐like rocks or rock‐like concretes; thus, they are of interest to geophysical and engineering communities (and their hybrids), especially in regard to natural or human‐made barriers for gases and fluids. A notable example of a gas that can be, or is desired to be, contained underground by rock formations and/or cemented structures is carbon dioxide (CO2 ). However, it is important to realize that some of the most relevant properties of a rock or concrete serving as a barrier may actually be evolving during exposure to CO2 . Consequently, there is a need to understand the processes involved if we are to accurately predict the long‐term efficacy of these seals. We injected CO2 into samples of cemented volcanic ash and subsequently monitored the changes in their permeability while they chemically reacted. Our observations indicate that this particular material, when located at sufficient depth in the subsurface, can serve as a barrier to CO2 ‐rich fluid flow. Key Points: Carbonation products block gas flow through lime‐cemented volcanic ash, making permeability a time‐dependent, rock physical property Cascading reaction rims of CaCO3 form upon repeated injection of CO2 Rapid depressurization of CO2 gas enhances the permeability of cemented volcanic ash via fracturing when it occurs at low effective stress